2020
DOI: 10.1016/j.jaip.2020.06.032
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Pneumonia in Hospitalized Asthmatic Patients Did Not Induce Severe Exacerbation

Abstract: What is already known about this topic? Patients with asthma are rare in epidemiological studies of severe acute respiratory syndrome coronavirus 2 pneumonia.What does this article add to our knowledge? Being asthmatic is not a risk factor for severe acute respiratory syndrome coronavirus 2.How does this study impact current management guidelines? Severe acute respiratory syndrome coronavirus 2 pneumonia may not induce severe asthma exacerbation.BACKGROUND: Viral infections are known to exacerbate asthma in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 38 publications
8
52
0
5
Order By: Relevance
“…A recent study showed that asthmatic patients are not at risk and do not develop severe SARS-COV-2 pneumonia compared to non-asthmatic patients [32]. In fact, we observed a low prevalence of asthmatic individuals (7.15%) among hospitalized COVID-19 patients, in agreement with the existing reports.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study showed that asthmatic patients are not at risk and do not develop severe SARS-COV-2 pneumonia compared to non-asthmatic patients [32]. In fact, we observed a low prevalence of asthmatic individuals (7.15%) among hospitalized COVID-19 patients, in agreement with the existing reports.…”
Section: Discussionsupporting
confidence: 92%
“… 16 , 17 , 19 , 20 Additionally, eosinopenia has been observed in patients with COVID-19, and more prominently this was represented in the more severe cases, stabilizing after clinical improvement. 17 , 21 , 22 This suggests that eosinophils could play a protective role against developing more severe clinical outcomes. 21 , 22 …”
Section: How Does Covid-19 Affect Individuals With Asthma?mentioning
confidence: 99%
“… 17 , 21 , 22 This suggests that eosinophils could play a protective role against developing more severe clinical outcomes. 21 , 22 …”
Section: How Does Covid-19 Affect Individuals With Asthma?mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with asthma have reduced susceptibility to SARS-CoV-2, and that asthma symptoms are not exacerbated by SARS-CoV-2 infection [43][44][45] . However, it has been suggested that a subset of asthma patients (Type-2 low asthmatics) who are more at risk of SARS-CoV-2 show higher ACE2 expression in bronchial epithelium, associated with upregulation of viral response genes 46 .…”
Section: Short and Long Ace2 Are Regulated Differently In Severe Asthmamentioning
confidence: 99%